(3JgPjH GdceGd aj CSeGA GdQLGds - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s; (3jMji Hf qMnHT Hf CejQc, CHh GdaJhM, TgGH GdOjf, GdSgQhQOj,J (B587 (3g` s ((3eMeO EHQGgje Hf ZfGje Hf GdegfOS s)
(3ChdgG (B:s
(3ef GdLQGM Hf CHj GdLQGM s
(3BNQgG (B:s
(3Edi GdMSf Hf YjSi GdbQTi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B99 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs